Atomic and molecular Auger decay in CHCl3 molecule. Issue 12 (January 2020) - Vasconcelos, D N; Santos, A C F; Morcelle, V; Macdonald, M A; Sant'Anna, M M; Tenório, B N C; Rocha, A B; Bonfin, V B; Appathurai, N; Zuin, L
Synopsis: The dissociation following Cl 2p core–shell excitation in CHCl3 molecule is studied. It is observed the presence of atomic Auger lines associated with the decay of dissociated Cl * atoms. Calculations were compared with the corresponding experimental photoexcited and photoionized spectra to study the competition between the atomic and molecular Auger decays.